Resiliensi Anak Pertama yang Menjadi Tulang Punggung Keluarga Ditinjau dari Coping Stres dan Dukungan Keluarga - Khusnul Mar’iyah; Mohammad Khasan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The firstborn child who acts as the family breadwinner carries a heavy economic responsibility, making them vulnerable to psychological distress and requiring the ability to bounce back and endure (resilience). This study aims to empirically examine the relationship between stress coping and family support with resilience in firstborn children who serve as family breadwinners. The research method used was quantitative correlational, with a sample of 120 respondents selected through a quota sampling technique. Data collection was conducted using a resilience scale, a stress coping scale, and a family support scale. The data were then analyzed using a two-predictor regression analysis technique. The results showed a very significant relationship between stress coping and family support simultaneously with resilience (R = 0,724; F = 64,430, p = 0,000), with an effective contribution of 52.4% (R2=0,524). Partially, there was a significant positive relationship between stress coping and resilience (r = 0,582; p = 0,000) as well as family support and resilience (r = 0,614; p = 0,000). The conclusion of this study is that adaptive stress coping and strong family support contribute significantly to increasing the resilience of firstborn children who take on the role of the family breadwinner.